2018
DOI: 10.1111/een.12694
|View full text |Cite
|
Sign up to set email alerts
|

Experimental warming disrupts reproduction and dung burial by a ball‐rolling dung beetle

Abstract: 1. Insects are sensitive to climate change. Consequently, insect‐mediated ecosystem functions and services may be altered by changing climates.2. Dung beetles provide multiple services by burying manure. Using climate‐controlled chambers, the effects of warming on dung burial and reproduction by the dung beetle Sisyphus rubrus Paschalidis, 1974 were investigated. Sisyphus rubrus break up dung by forming and rolling away balls of manure for burial and egg deposition.3. To simulate warming in the chambers, 0, 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 47 publications
1
28
2
Order By: Relevance
“…Droughts and warming can also affect the survival and brood production in adult dung beetles. Previous research has found a large number of beetles reabsorbing their oocytes—suggested as physiological response to heat and water stress (Tyndale‐Biscoe, Wallace, & Walker, ), while artificial warming experiments have shown that hotter and drier conditions affected the relative survival and emigration of two dung beetle species (Holley & Andrew, ), as well as disrupted dung beetle reproduction via a decline in ball burial (Holley & Andrew, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Droughts and warming can also affect the survival and brood production in adult dung beetles. Previous research has found a large number of beetles reabsorbing their oocytes—suggested as physiological response to heat and water stress (Tyndale‐Biscoe, Wallace, & Walker, ), while artificial warming experiments have shown that hotter and drier conditions affected the relative survival and emigration of two dung beetle species (Holley & Andrew, ), as well as disrupted dung beetle reproduction via a decline in ball burial (Holley & Andrew, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although spatial patterns of movement can vary among species (Silva & Hernández, 2015), most dung beetles are poor fliers-for example, having an estimated movement of 90 m in 48 hr (Silva & Hernández, 2015) and may not be able to escape understory fires; (Holley & Andrew, 2019b).…”
Section: Direct Drivers Of Change In Dung Beetle Communitiesmentioning
confidence: 99%
“…). Our previous study found that a 2–4°C increase in temperature reduced dung ball burial by S. rubrus , which may reduce egg laying in this species (Holley & Andrew ). Consequently, ecosystem service provision and reproduction by S. rubrus may be vulnerable to the effects of climate warming.…”
Section: Introductionmentioning
confidence: 92%
“…To address the accumulation of unburied cattle manure, exotic species of dung beetles that are adapted to process bovine dung have been released into Australia (Edwards ). We have previously assessed the effect of warming on ecosystem service provision by Sisyphus rubrus (Coleoptera: Scarabaeidae; Holley & Andrew ), a ball‐rolling dung beetle native to southern Africa that was introduced into Australia between 1973 and 1980. Sisyphus rubrus is found throughout much of Queensland and parts of New South Wales (Edwards ; Edwards et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation